InGaN quantum dots grown by MOVPE via a droplet epitaxy route - Rice, J; Oliver, R; Robinson, J; Smith, J; Taylor, R; Briggs, G; Kappers, M; Humphreys, C; Yasin, S (2004)
A novel method for the growth of InGaN quantum dots (QDs) by metal-organic vapour phase epitaxy (MOVPE) is described. A thin InGaN epilayer is grown on a GaN buffer layer and then annealed at growth temperature in molecular nitrogen inducing QD formation. The photolummescence from the dot ensemble is bright and comparable in intensity to that from a quantum well. Micro-photoluminescence studies of these QDs reveal sharp peaks with typical line widths of similar to250 mueV at 4.2 K. Time-resolved photoluminescence suggests that the excitons in these structures have lifetimes in excess of 2 ns at 4.2 K. (C) 2003 Elsevier B.V. All rights reserved.